THE IMPACT OF EARTHQUAKE ON CHILD TEST SCORE - Eny Sulistyaningrum (Faculty of Economics and Business, Universitas Gadjah Mada, 2017)
Natural disasters always affect different aspects of individual life. They affect almost every part of life, such as the emotional, economic, physical, social, and environmental aspects. Children are believed to be very vulnerable to disasters. The increasing frequency of disasters and the intensity of their destruction motivate an analysis of the impacts of disasters, especially on education, for children. This paper uses a micro level survey data set from the Indonesian Family Life Survey (IFLS) which covers approximately 83% of the Indonesian population within the survey area. The main objective of this paper is to examine the effects of earthquakes on students’ performance, measured by their child test scores. This type of disaster was chosen because of its intensity, as measured by the percentage of people killed, and the percentage of people evacuated. Moreover, we also investigate the children who took the test immediately after the earthquake and compare their scores with those whose tests were a year after the earthquake. Arguably an earthquake is an exogenous event, so we use the exogenous variation of earthquake as a natural experiment design to estimate the effect of earthquakes on child test scores. A Difference in Difference model (DiD) can be used for estimating if a certain group is exposed to the causal variable of interest, such as an earthquake, and other groups are not. The results confirm that child test scores are significantly affected by earthquakes.